A Firm-Level Analysis of Development Banks in Europe - Marco Frigerio; Daniela Vandone (Vierteljahrshefte zur Wirtschaftsforschung, 2020)
We perform a cross-country firm-level analysis of all development banks headquartered in Europe. The goal is to investigate their financial profile and efficiency characteristics and to shed light on some crucial issues, which may underline their capacity to raise external sources of finance in addition to capital contributions from shareholder governments (e. g. their capital generation and cost efficiency, the quality of their loan portfolio, the composition of their sources of finance). A financial statement analysis of their accounting features is cogent in the light of the relevance attributed by European policy makers to the economic and financial sustainability of development banks, given the key role they have been called to play in the European economy since the 2008 crises. Indeed, although development banks have goals that go beyond profitability, they need to combine their socio-economic goals with conditions of efficiency and profitability, in order to "stand on their own feet" and secure a reasonable level of financial strength and stability. We first map all development banks headquartered in Europe. We then collect financial information within the reference period 2008–2018 for the whole population of development banks. We also split the sample according to size, in order to assess their dimensional heterogeneity. This study provides policymakers with quantitative information on the economic and financial profile of contemporary promotional financial institutions, which may be valuable in the current debate on their role and relevance in Europe. – – Diese Studie liefert auf Unternehmensebene eine länderübergreifende Analyse aller Entwicklungsbanken mit Hauptsitz in Europa. Ziel ist es, das finanzielle Profil und die Effizienzmerkmale der Entwicklungsbanken herauszuarbeiten und ihre Fähigkeit zur Beschaffung externer Finanzierung zu beleuchten. Eine solche Bilanzanalyse ist zwingend, angesichts der Relevanz, die der wirtschaftlichen und finanziellen Nachhaltigkeit von Entwicklungsbanken beigemessen wird, und angesichts der Schlüsselrolle, die Entwicklungsbanken seit der Krise von 2008 in der europäischen Wirtschaft spielen. Obwohl Entwicklungsbanken Ziele verfolgen, die über die Rentabilität hinausgehen, müssen sie ihre sozioökonomischen Ziele mit Effizienz und Rentabilität kombinieren, um "auf eigenen Beinen stehen" und ein angemessenes Maß an Finanzkraft und Stabilität sicherstellen zu können. Politischen Entscheidungsträgern werden damit quantitative Informationen zum wirtschaftlichen und finanziellen Profil an die Hand gegeben, die für die aktuelle Debatte über die Rolle von Entwicklungsbanken wichtig sind.
Keywords: G21; O16; L32; 330; Competition; Covid-19; development bank; digitalisation; EIB; green bond; infrastructure; social inclusion; structural transformation